Household expenditure on food away from home by type of meal in Malaysia - Md. Nurul Islam, Gazi; Tai, Shzee Yew; Raja Abdullah, Nik Mustapha; Mohd Noh, Kusairi (Universiti Putra Malaysia Press, 2010)
This paper analyses the household food-away-from-home (FAFH) expenditure pattern in Malaysia. For this purpose, the Tobit model was used to quantify the responsiveness of households' expenditure on FAFH to changes in their income and the household characteristics. The results show that households` FAFH expenditure has increased due to rise in income and changing lifestyle. Meanwhile, the household income has statistically significant influence on the FAFH expenditure for all types of meals, except for breakfast, although the FAFH expenditure for breakfast is positive. The positive effect of the total household income shows Malaysian households spent more by eating out as they have to spend more time at work and less time to prepare food at home. Breakfasts and lunches away from home have positive and inelastic income. The results indicate that household members have less choice but to consume breakfast and lunch away from home as their workplaces are usually far away from their homes and thus consume these meals at home are not cost-effective. They have greater flexibility in making decisions whether to consume at home or away from home for dinner and other meal. The estimated conditional and unconditional income elasticity for the households` FAFH expenditure for all types of meals shows that the FAFH expenditures by Malaysian households are income inelastic. This implies that the growth in the FAFH sector will largely be driven by household demographics, ethnic characteristics and region in Malaysia. The government should take appropriate measures to ensure that the meals are of high nutritious values, safe, and reasonably priced.